Exponential Regulation Control of a Quadrotor Unmanned Aerial Vehicle With a Suspended Payload - Yang, Sen; Xian, Bin (IEEE transactions on control systems technology, 2020)
This brief focuses on the control design for the aerial cargo transportation system that consists of a quadrotor unmanned aerial vehicle (UAV) and a cable-suspended payload. The underactuated properties associated with the system dynamics bring great challenges for the control development. Partial feedback linearization methodology is employed to formulate a nonlinear controller that yields an exponential regulation result of the quadrotor UAV position, while the swing motion of the payload is suppressed exponentially fast. A Lyapunov-based stability analysis is included to prove the convergence of the position error and the local exponential stability of the closed-loop system. Real-time experiments are performed on a self-built UAV testbed to validate the performance of the proposed control strategy.